Safeguards Assessments : 2013 Update. (Policy Papers; Policy Paper, 2013)
The safeguards policy, introduced in 2000, is designed to reduce the risks of misuse of Fund resources and misreporting of program monetary data to the Fund. It supports the Fund's approach to prudent lending and complements other safeguards, including program design, conditionality, and access limits. Safeguards assessments are required for almost all member countries seeking Fund financing, and are followed by a period of monitoring for as long as Fund credit is outstanding.